Pharmacokinetic and metabolic investigations of mycophenolic acid in pediatric patients after renal transplantation: implications for therapeutic drug monitoring - Oellerich, Michael; Shipkova, Maria; Schütz, Ekkehard; Wieland, Eberhard; Weber, Lutz T.; Tönshoff, Burkhard; Armstrong, Victor W. (Therapeutic drug monitoring, 2000)
The need for mycophenolic acid (MPA) monitoring is still under discussion. Key issues for the PK/PD relationships of this drug are: the role of metabolites, the usefulness of AUC versus predose levels, and the need to monitor the free concentration of MPA (f-MPA). Recent advances have revealed that, in addition to 7-O-MPAG, three additional MPA metabolites are present in the plasma of transplant recipients. One of these metabolites (M-2), identified as an acyl glucuronide of MPA, was found to inhibit IMPDH-II in vitro. This active metabolite was also found to cross-react in the Emit assay for MPA. In an ongoing multicenter study, the authors are evaluating the relevance of monitoring total (t-MPA) and free mycophenolic acid (f-MPA) in pediatric renal transplant recipients.
Der Verfasser "Lutz Weber" wurde in der Verfasserliste falsch geschrieben
Gesehen am 26.01.2021